2020
DOI: 10.3389/fimmu.2020.00375
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Generation of Human Allospecific Induced Tregs With Functional Stability for Use in Immunotherapy in Transplantation

Abstract: Regulatory T cells play an important role in the control of autoimmune diseases and maintenance of tolerance. In the context of transplantation, regulatory T cells (Tregs) have been proposed as new therapeutic tools that may induce allospecific tolerance toward the graft, avoiding the side effects induced by generalized immunosuppressors. Although most clinical trials are based on the use of thymic Tregs in adoptive therapy, some reports suggest the potential use of in vitro induced Tregs (iTregs), based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…Our study is in line with a previous report showing the effect of rapamycin on Treg stability through preventing the production of pro-inflammatory cytokines in expanded Tregs and inhibiting the conversion of Tregs toward an inflammatory phenotype (60). In addition, the expansion of allospecific nTregs in the presence of IL-2 alone was able to maintain >80% FOXP3 + (Figure S9D), while both the induction and the maintenance of FOXP3 in expanded allospecific iTregs (22) and polyclonal iTregs (61) were shown to be highly dependent on the presence of TGF-b and rapamycin in the in cultures.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study is in line with a previous report showing the effect of rapamycin on Treg stability through preventing the production of pro-inflammatory cytokines in expanded Tregs and inhibiting the conversion of Tregs toward an inflammatory phenotype (60). In addition, the expansion of allospecific nTregs in the presence of IL-2 alone was able to maintain >80% FOXP3 + (Figure S9D), while both the induction and the maintenance of FOXP3 in expanded allospecific iTregs (22) and polyclonal iTregs (61) were shown to be highly dependent on the presence of TGF-b and rapamycin in the in cultures.…”
Section: Discussionsupporting
confidence: 93%
“…With this protocol, we achieved an expansion from 1,800-to 2,300-fold allo Tregs after 4 weeks of culture (Figure 2A), while previous studies reported an expansion ranging from 8-to 780-fold for 12-42 days of culture [revised in (19)]. These results are similar to those obtained in the expansion of allospecific iTregs using a slightly modified protocol, favoring the enrichment of FOXP3 + iTregs (from 60% to >90% of FOXP3 + cells) (22). Moreover, expanded allo Tregs displayed an increase in the expressions of CD25 and CTLA-4, in correlation with the increase of FOXP3, which directly upregulated the transcription of both molecules by binding to the Il2ra and Ctla4 loci (42).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…iTregs induced with TGF-b in the presence of all-trans retinoic acid (ATRA) and rapamycin demonstrated robust suppressive function in vitro but not in vivo, in the humanized GVHD mouse model (121). Interestingly, allospecific iTregs that were induced with TGF-b1, IL-2, and ATRA in the presence of allogeneic monocyte-derived dendritic cells, can specifically suppress donor allo-responses but not third-party allo-responses, and maintain suppressive function in the presence of pro-inflammatory cytokines, despite methylation of the FOXP3 TSDR (122).…”
Section: Car-tregsmentioning
confidence: 99%